TAHAPAN PEMBUATAN KEBIJAKAN PUBLIK SEBAGAI LANDASAN PENGAMBIL KEBIJAKSANAAN - Abdullah Abdul; Alchonity Harika Fitri; Ayu Mustika Sari; Nurhizrah Gistituati; Rusdinal Rusdinal (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
The purpose of this research is to understand the various stages of public policy making so as to make it easier to analyze complex problems so that they can be formulated into a policy for a public leader. Public policy studies seek to review shared theories and processes that occur in public policy. It can be said that public policy cannot be separated from the process of policy formation itself, thus, one of the objectives of the study of public policy is to analyze how the stages of the process of forming public policy are so that a certain policy is realized. These stages are summarized as a process of public policy making cycle. Each stage in the process of forming public policy contains various steps and methods in more detail. The stages involved in making a public policy have various benefits and consequences from the existence of the process, especially for actors making public policies